Analyzing the Effect of Tax Risk on Audit Report Timeliness: Evidence of Audit Committee Moderation - Tantya, Fristhienty; Tanujaya, Kennardi; Dewi, Sari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
Timeliness in audited financial reporting is a critical element of credible corporate disclosure. However, heightened tax-related uncertainty can increase audit complexity and extend the completion period of audit procedures. This study investigates whether tax risk contributes to audit report lag and assesses the moderating role of audit committees in this association. Using panel data from 925 firm-year observations of non-financial companies listed on the Indonesia Stock Exchange between 2019 and 2023, the hypotheses were examined through moderated regression analysis. The empirical results reveal that firms exposed to greater tax risk experience significantly longer audit delays, suggesting that auditors require more extensive verification and judgment when auditing aggressive or uncertain tax positions. In contrast, an effective audit committee is found to mitigate this effect by strengthening monitoring functions, improving communication with external auditors, and ensuring the availability of reliable information during the audit process. This study contributes to the governance and auditing literature by providing evidence from an emerging market that emphasizes the role of tax risk in shaping reporting timeliness and highlights the governance mechanisms that can reduce delays. The findings have practical implications for regulators and corporate boards to improve audit committee effectiveness in supporting higher transparency and reporting credibility.